Kemâl Ahmed Dede's verse narrative Tercüme-i Menâkıb-ı Mevlânâ (a verse version in the Menâkıbü'l-Ârifîn tradition), part II : analysis, transcription - Kemâl Ahmed Dede, 1558-1601. ([Harvard])
ix, 336 s.